Black rockfish C-type lectin, SsCTL4: A pattern recognition receptor that promotes bactericidal activity and virus escape from host immune defense. Issue 79 (August 2018) - Xue, Du; Guang-hua, Wang; Yan-li, Su; Min, Zhang; Yong-hua, Hu
Abstract: C-type lectin (CTL) is an immune receptor and is received extensive attention of its important roles in immune response and immune escape. Some CTL, such as CTL4, has been well characterized in human and several other mammals, but much less documentation exists about the immunological function of CTL4 in lower vertebrates. In the present study, a C-type lectin domain family 4 member, SsCTL4, which is also high homology with CD209 antigen-like protein, from the teleost fish black rockfish ( Sebastes schlegelii ) was identified and examined at expression and functional levels. The open reading frame of SsCTL4 is 765 bp, and the deduced amino acid sequence of SsCTL4 shares 78%–84% overall identities with the C-type lectin of several fish species. In silico analysis identified several conserved C-type lectin features, including a carbohydrate-recognition domain and four disulfide bond-forming cysteine residues. Expression of SsCTL4 occurred in multiple tissues and was upregulated during bacterial and viral infection. Recombinant SsCTL4 (rSsCTL4) exhibited apparent binding activities against bacteria ( Edwardsiella tarda and Vibrio anguillarum ) and virus (infectious spleen and kidney necrosis virus, ISKNV). rSsCTL4 was able to agglutinate the Gram-negative and Gram-positive bacteria in a Ca 2+ -dependent manner. The agglutinating ability of rSsCTL4 was abolished in the absence of calcium or presence of mannose. rSsCTL4 also increased macrophage bactericidal activity. In the presence of rSsCTL4, fish exhibited enhanced resistance against bacterial infection but increased susceptibility to viral infections. Collectively, these results indicate that SsCTL4 serves as a pattern recognition receptor that not only promotes bactericidal activity, but may also serve as targets for virus manipulation of host defense system. Highlights: SsCTL4 has a C-type lectin-like domain. Expression of SsCTL4 was upregulated during bacterial and viral infection. rSsCTL4 exhibited apparent binding activities against bacteria and virus. rSsCTL4 increased macrophage bactericidal activity. rSsCTL4 enhanced fish resistance against bacterial infection but increased susceptibility to viral infections.